BUILDING STUDENTS’ CULTURAL AWARENESS THROUGH PROJECT-BASED LEARNING - Kenjayeva Marxabo Majidvoy qizi; Jonibekova Mehriniso Umarbek qizi (PEDAGOGS, 2024)
Abstract. In an increasingly interconnected world, cultivating cultural awareness in students is crucial for developing global citizens who can navigate diverse perspectives, appreciate different values, and contribute positively to a multicultural society. Project-Based Learning (PBL) offers a dynamic and engaging approach to education that effectively fosters this crucial skill. By immersing students in authentic, real-world projects that explore diverse cultures, PBL empowers them to gain deeper insights, challenge stereotypes, and develop empathy and understanding. This article explores the significance of cultural awareness, examines how PBL provides a powerful framework for cultivating it, delves into practical implementation strategies, and outlines the substantial benefits for students. Through authentic projects, student voice, collaboration, inquiry, and ongoing assessment, PBL creates a learning environment where students can challenge their own biases, develop communication skills, cultivate empathy, and develop a broader worldview. This article ultimately advocates for the integration of PBL as a strategic tool for building cultural awareness in students, preparing them for success in an increasingly globalized and diverse world.